2018
DOI: 10.1016/j.schres.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The aprosody of schizophrenia: Computationally derived acoustic phonetic underpinnings of monotone speech

Abstract: Findings could represent a step toward developing new methods for measuring and tracking the severity of this specific negative symptom using acoustic phonetic parameters; such work is relevant to other psychiatric and neurological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 34 publications
4
46
0
Order By: Relevance
“…Applications for understanding SMI are relatively limited, though links between reduced MFCC and clinically rated depression in adults (e.g., with 80% classification accuracy 46 ) and adolescents (e.g., with 61.1% classification accuracy 47 ) have been observed. Moreover, Compton et al 12,42 have demonstrated statistically significant relationships between formant frequencies and clinically rated negative symptoms (e.g., r = −0.45 12 ). In short, clinicians appear to be intuitively evaluating a much broader feature set than is included in most prior studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Applications for understanding SMI are relatively limited, though links between reduced MFCC and clinically rated depression in adults (e.g., with 80% classification accuracy 46 ) and adolescents (e.g., with 61.1% classification accuracy 47 ) have been observed. Moreover, Compton et al 12,42 have demonstrated statistically significant relationships between formant frequencies and clinically rated negative symptoms (e.g., r = −0.45 12 ). In short, clinicians appear to be intuitively evaluating a much broader feature set than is included in most prior studies.…”
Section: Discussionmentioning
confidence: 98%
“…These features have not been typically examined in the context of SMI, as they are not captured by the VOXCOM or CANS systems (refs. 40,41 ; but see 12,42 for an exception). Collectively, these features concern the spectral quality and richness or speech, reflecting the involvement of a much broader vocal system than those typically involved in psychopathology research, e.g., "pitch" and "volume".…”
Section: Discussionmentioning
confidence: 99%
“…A different approach involves the use of automated analysis of speech to identify acoustic features of vocal production, arguably with a greater reliability, sensitivity and validity. However, such studies have so far reported smaller and seemingly more contradictory findings: some indicate slower speech (Tavano et al, 2008), more pronounced pauses (Cannizzaro et al, 2005;Martínez-Sánchez et al, 2015;Rapcan et al, 2010) and reduced prosodic variability (Compton et al, 2018;Martínez-Sánchez et al, 2015;; while others indicate no reliable acoustic differences between 6 VOICE IN SCHIZOPHRENIA: REVIEW AND META-ANALYSIS individuals with schizophrenia and HC (Cohen et al, 2016;Docherty, 2012;Meaux et al, 2018). A meta-analysis of 13 studies suggests large differences between individuals with schizophrenia and HC on pause and speech duration, and more modest on intensity and pitch variability.…”
Section: Introductionmentioning
confidence: 99%
“…Vocal acoustic analysis is also capable of measuring the severity of negative symptoms such as aprosodia. Compton et al (2018) analyzed audio recordings of schizophrenic patients with aprosodia, schizophrenic patients without aprosodia, and healthy controls, and compared variability in pitch (F0), first (F1) and second (F2) formants, and intensity/loudness. Their results showed significant differences among groups, with the group with aprosodia showing reduced variability in pitch, F2, and intensity/loudness than other groups.…”
Section: Related Workmentioning
confidence: 99%